Pristimerin, a triterpene that inhibits monoacylglycerol lipase activity, prevents the development of paclitaxel-induced allodynia in mice - Al-Romaiyan, Altaf; Masocha, Willias (Frontiers in Pharmacology, 2022)
Background: Triterpenes such as euphol and pristimerin, which are plant secondary metabolites, were the first to be characterized as monoacylglycerol lipase (MAGL) inhibitors. MAGL inhibitors alleviate chemotherapy-induced neuropathic pain (CINP) in rodent models. Pristimerin has been shown to have additive anticancer activity with paclitaxel, a chemotherapeutic drug. However, the activity of pristimerin on CINP has not been evaluated. Objectives: The aims of this study were to evaluate whether various triterpenes had activity against recombinant human MAGL and MAGL activity in mouse tissues, and whether pristimerin could prevent development of paclitaxel-induced mechanical allodynia. Methods: The effects of four triterpenes betulinic acid, cucurbitacin B, euphol, and pristimerin on the activity human recombinant MAGL and MAGL activity of mice brain and paw skin tissues were evaluated using MAGL inhibitor screening and MAGL activity assay kits. The effects of treatment of female BALB/c mice with pristimerin intraperitoneally on the development of paclitaxel-induced mechanical allodynia were assessed using the dynamic plantar aesthesiometer and on nuclear factor-2 erythroid related factor-2 (Nrf2) gene expression in the paw skin were evaluated by real time polymerase chain reaction. Results: Pristimerin inhibited the human recombinant MAGL activity in a concentration-dependent manner like JZL-195, a MAGL inhibitor. Betulinic acid, cucurbitacin B and euphol inhibited human recombinant MAGL activity but their effects were not concentration dependent and were less to that of pristimerin. Pristimerin inhibited both mouse brain and paw skin MAGL activity in a concentration-dependent manner. Paclitaxel induced mechanical allodynia and increase in MAGL activity in the paw skin. Treatment with pristimerin prevented the development of paclitaxel-induced mechanical allodynia and the paclitaxel-induced increase in MAGL activity. Pristimerin significantly upregulated mRNA expression of Nrf2, a regulator of endogenous antioxidant defense. Conclusion: These results indicate that triterpenes inhibit human recombinant MAGL activity with varying degrees. Pristimerin inhibits both mouse brain and paw skin MAGL activity in a concentration-dependent manner, prevents both the development of paclitaxel-induced mechanical allodynia and the associated increase in MAGL activity in the paw skin, and might protect against paclitaxel-induced oxidative stress. Co-treatment with pristimerin and paclitaxel could be useful in the treatment of cancer and prevention of CINP.